PENGARUH EXPERIENTIAL MARKETING DAN CONTENT MARKETING TERHADAP CUSTOMER ENGAGEMENT PADA INSTAGRAM @KLINIK_KECANTIKAN_LUXURY DI KOTA BIMA - Ismunandar Ismunandar; Alwi Alwi (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2025)
This research aims to analyze the influence of experiental marketing and content marketing on customer engagement on the Instagram account @klinik_kecantikan_luxury located in Bima City, West Nusa Tenggara. Instagram is a popular social media platform used as a marketing channel. Research data was obtained through a questionnaire distributed to 96 respondents who were followers of the Instagram account @klinik_kecantikan_luxury and had used the services of the Luxury Clinic at least twice. The results of the analysis show that experiential marketing and content marketing have a significant influence on customer engagement at @klinik_kecantikan_luxury. The implication of this research is the importance of companies providing a good experience to consumers and designing and delivering interesting and relevant content to increase customer engagement. An effective content marketing strategy can increase customer loyalty and help companies achieve marketing goals more efficiently.